Resveratrol and Curcumin for Chagas Disease Treatment—A Systematic Review - Imperador, Carlos Henrique Lima; Scarim, Cauê Benito [UNESP]; Bosquesi, Priscila Longhin [UNESP]; Lopes, Juliana Romano [UNESP]; Neto, Augusto Cardinalli; Giarolla, Jeanine; Ferreira, Elizabeth Igne; Santos, Jean Leandro dos [UNESP]; Chin, Chung Man [UNESP] (MDPI, 2022)
Chagas disease (CD) is a neglected protozoan infection caused by Trypanosoma cruzi, which affects about 7 million people worldwide. There are two available drugs in therapeutics, however, they lack effectiveness for the chronic stage—characterized mainly by cardiac (i.e., cardiomyopathy) and digestive manifestations (i.e., megaesophagus, megacolon). Due to the involvement of the immuno-inflammatory pathways in the disease’s progress, compounds exhibiting antioxidant and anti-inflammatory activity seem to be effective for controlling some clinical manifestations, mainly in the chronic phase. Resveratrol (RVT) and curcumin (CUR) are natural compounds with potent antioxidant and anti-inflammatory properties and their cardioprotective effect have been proposed to have benefits to treat CD. Such effects could decrease or block the progression of the disease’s severity. The purpose of this systematic review is to analyze the effectiveness of RVT and CUR in animal and clinical research for the treatment of CD. The study was performed according to PRISMA guidelines and it was registered on PROSPERO (CDR42021293495). The results did not find any clinical study, and the animal research was analyzed according to the SYRCLES risk of bias tools and ARRIVE 2.0 guidelines. We found 9 eligible reports in this study. We also discuss the potential RVT and CUR derivatives for the treatment of CD as well.
Keywords: anti-inflammatory; Chagas disease; curcumin; resveratrol; Trypanosoma cruzi